Letter (copy) : Article - Tewson, Vincent
026-0100-001 International. HVT/AC/DT/927. 9th May, 1939. Mr. W. Carrillo, Bonnington Hotel, Southampton Row, LONDON, W.C.1. Dear Comrade Carrillo, ARTICLE. I have received your letter of 8th May with the enclosed article which we are having translated with a view to publication in "Labour". Advantage is being taken, as you know, of personal contacts with Schevenels and Jouhaux this week for the purpose of discussing the possibility of your joining your family in France. Cordially reciprocating your good wishes, Yours sincerely, Assistant Secretary. 292/946/26/100